Intensive grazing system increases milk productivity of Holstein and Jersey-Holstein crossbred dairy cows. - OLIVEIRA, P. P. A. (2016)
In Brazil, despite the lack of accurate statistics on the contribution of each type of system in total milk production, it is known that pastures represent the main feed source in most production systems (IBGE, 2010). However, a major concern with respect to this factor is related to the potential environmental impact the degradation of thousands of hectares of these pastures may have.